Die Finanzzentren Frankfurt am Main und Zürich und ihr Umland - ein Vergleich regionaler Strukturen - Langhagen-Rohrbach, Christian (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
During the last few centuries, urban landscape has changed significantly: "world cities" have become international business centres. Most of them have a large hinterland that fulfil supplementary tasks for the city itself. The hinterland of Frankfurt/Main - the Rhine-Main-Region - and of Zurich - the Kanton Zurich - give an example of the new regional challenges and problems that arise from the core-city's status as a "world city".
Keywords: centralna naselja; finančne storitve; Frankfurt; funkcije; identiteta; mesta; urbana geografija; urbani razvoj; Zürich